The use of sugar beet pulp stillage for co-digestion with sewage sludge and poultry manure. Issue 10 (October 2019) - Borowski, Sebastian; Kucner, Marcin
The anaerobic mesophilic co-digestion of sugar beet pulp stillage with poultry manure and municipal sewage sludge was investigated in this study. The sugar beet pulp stillage (SBPS) mono-digestion failed owing to an accumulation of volatile fatty acids, leading to a pH value lower than 5.5. A 20% addition of poultry manure to stillage allowed for stable digestion performance despite high volatile fatty acid (total volatile fatty acids) concentrations of 5500–8500 g m −3 with propionic acid being the predominant one and constituting 72%–76% total volatile fatty acids. For this mixture, the maximum methane production of 418 dm 3 kgVSfed −1 was achieved when the reactor was operated at a solids retention time of 20 days and an organic loading rate of 4.25 kgVS m −3 d −1 . The co-digestion of stillage with 60% municipal sewage sludge gave the average methane yield of around 357 dm 3 kgVSfed −1 for all operational conditions applied, however, the methane percentage of biogas (up to 70%) was far greater than the corresponding values obtained for sugar beet pulp stillage–poultry manure co-digestion. Neither ammonia nor volatile fatty acids destabilised the biogas production, and the volatile fatty acid profile showed the dominance of acetic acid (72%–82% total volatile fatty acids) followed by propionic and butyric acids.